Building Information Modeling (BIM) Utilization for 3D Fiscal Cadastre - Sadikin Hendriatiningsih; Andri Hernandi; Asep Yusup Saptari; Ratri Widyastuti; Dhendy Saragih (Indonesian Journal of Geography, 2019)
Parcels data in Indonesia are still stored in 2-dimensional (2D) geometry which are integrated with other attribute data, such as the case with the Directorate of Land and Building Tax Indonesia. Whereas, building taxes assessment refers to a number of details that require the information to be stored in 3-dimensional (3D) forms. This study aims at the use of Building Information Modeling (BIM) technology, which widely used in building asset management in 3D. This research illustrates the usability of the role of BIM in assessing and managing building taxes in Indonesia. The point clouds were obtained using Terrestrial Laser Scanner (TLS) technology. The point clouds processed so that it can form 3-dimensional geometrical apartment. The attributes of the 3-dimensional model integrated with the geometric model using the BIM concept. The results analyzed to assess whether BIM concept was able to fulfill the needs of the 3D fiscal cadastre in Indonesia.